2023
DOI: 10.3390/ijerph20020969
|View full text |Cite
|
Sign up to set email alerts
|

Research on Biogas Yield from Macroalgae with Inoculants at Different Organic Loading Rates in a Three-Stage Bioreactor

Abstract: Macroalgae can be a viable alternative to replace fossil fuels that have a negative impact on the environment. By mixing macroalgae with other substrates, higher quality biogas can be obtained. Such biogas is considered one of the most promising solutions for reducing climate change. In the work, new studies were conducted, during which biogas yield was investigated in a three-stage bioreactor (TSB) during the anaerobic digestion of Cladophora glomerata macroalgae with inoculants from cattle manure and sewage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The concentrations of C and N were determined using an EA 3000 elemental composition analyzer (Eurovector, Pavia, Italy). The research results showed that, in the three-stage bioreactor, ΔC reached 10.0 ± 0.03 g/kg TS d and ΔN-0.3 ± 0.001 g/kg TS d. These results were obtained when the initial Cbefore of the substrate supplied to the TSB was 650.0 ± 19.5 g/kg TS, and the Nbefore was 25.0 ± 0.1 g/kg TS [22]. Using these data, the prospects for the use of methanogenesis products as organic fertilizers were evaluated, taking into account the carbon-to-nitrogen (C/N) ratio of the digested substrate in the TSB.…”
Section: Biomass Methanization In a Three-stage Bioreactormentioning
confidence: 81%
See 1 more Smart Citation
“…The concentrations of C and N were determined using an EA 3000 elemental composition analyzer (Eurovector, Pavia, Italy). The research results showed that, in the three-stage bioreactor, ΔC reached 10.0 ± 0.03 g/kg TS d and ΔN-0.3 ± 0.001 g/kg TS d. These results were obtained when the initial Cbefore of the substrate supplied to the TSB was 650.0 ± 19.5 g/kg TS, and the Nbefore was 25.0 ± 0.1 g/kg TS [22]. Using these data, the prospects for the use of methanogenesis products as organic fertilizers were evaluated, taking into account the carbon-to-nitrogen (C/N) ratio of the digested substrate in the TSB.…”
Section: Biomass Methanization In a Three-stage Bioreactormentioning
confidence: 81%
“…Studies have shown that high biogas yields can be achieved in a three-stage bioreactor. By using this type of bioreactor, up to 15% more biogas is extracted, and due to its structural features, the energy costs of bioreactor operation are reduced [21,22]. A three-stage bioreactor could be a promising tool for fertilizer production from the excess plant biomass of the Sea of Azov.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation chamber prevents oxygen from entering the second chamber together with the biomass. From the preparation chamber, the biomass is fed to the secondary chamber, where the substrate is shifted from aerobic (containing dissolved oxygen) to anaerobic conditions [ 21 ]. Previous research has shown that methanogenesis works effectively when the temperature is maintained at 37 °C [ 4 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Improving biogas recovery from anaerobic digestion systems represents another hotspot for further research. Two main areas attracting increased research in this aspect are process enhancement through optimising key parameters such as digestion time, process stability, biogas yield and rate, and exploring the use of new and improved microbial inoculants (Zagorskis et al 2023 ). Recent studies have been conducted on the optimisation of the systems for biogas generation from anaerobic digestion by increasing the organic content of feedstock (Freund et al 2020 ), through modelling the energy generation with machine learning algorithms (Kerem and Yuce 2023 ), biogas steam reforming (Park et al 2020 ), and combined optimisation with nitrogen removal (Vergara-Araya et al 2022 ).…”
Section: Future Directions Of ‘Wastewater To Energy’ Researchmentioning
confidence: 99%